On key controversies around estimations of environmental hazards and their removal - Gałuszko, Konrad (Studia Ecologiae et Bioethicae, 2003)
The key dissents on the estimation of environmental pollution between some humanists, ecophilosophers, especially devotees of deep ecology and its mass media supporters, and experimental scientists chiefly chemists and toxicologists are presented by a discussion of the most important problems: human health risk from food and nutrition, the expansion of new biological agents (pathogens), fears of chemical and physical agents stimulated opinions of toxicologists (ecotoxicologists) about most of the compounds for food preservation, antioxidants, pesticides, engine fuel components, metals. Subsequently to the above were discussed: the criticism of some misconceptions and the evolution of scientists. opinions about derivations of the greenhouse effect, toxicity and carcinogenesis criteria, evidence supporting the threshold dose versus the linear hypothesis at the evaluation of harmful environmental effects, examples of ecological utopia assuming a possibility of “life in the world without toxins”, the consequences of acts of law created with the idea, untrustworthy examples of alleged hazards, Poland’s law delay with the assimilation of the new toxicological and carcinogenesis evidence, DDT application dilemma concerned with the latter, the acceptance of the threshold dose also for radioactivity, the latest news about ravages of the Chernobyl catastrophe, the author’s belief in better cooperation of humanists, ecophilosophers, scientists and mass media people to create sensible social attitudes of the public in the face of the ecological and civilization crisis.